Driving Forces: Generational Differences on the Purchasing Behavior of Investment Assets among Gen Y and Gen Z - Karl Nikolai Quetua; Maria Clarizze Jade Juan; Gheena Rhae Mariah Katipunan; Clyde Marcus Velasco; Antonio Jr. Etrata (MEC-J (Management and Economics Journal), 2023)
With the rising numbers and interest in the financial literacy of Filipinos, more and more people are delving into investment assets. In this case, investment firms in the Philippines must discover new methods to address the current demand for investment assets better and plan effective strategies. This study aims to identify the purchasing behavior and factors influencing investment intention among Gen Y and Z investors. In order to assess the generational differences in behavioral patterns, the researchers used a quantitative approach using the convenience sampling technique for data collection. The data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The data collected in this research will help the firms know the behavior of their target market. Thus, acquiring the right strategies would increase sales of the said investment firms and help them determine the appropriate target market. This research shows that only financial literacy has a significant relationship with the investment purchasing behavior of both Gen Y and Gen Z investors, and there is no significant difference between their investment intentions. In order to influence both generations, marketing promotions of investment firms must appeal to the investors' prior investment knowledge. The results of this study will help the firms know the behavior of their target market, and thus, acquiring the right strategies would lead to the increase of sales of the said investment firms and would help them determine the appropriate target market.